1992
DOI: 10.1515/cclm.1992.30.9.503
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of the Mode of Action of Bacillus Calmette-Guérin-Therapy in Bladder Cancer Treatment, Especially with Regard to the Role of Fibronectin

Abstract: Summary:The interaction between Bacillus Calmette-Guerin (BCG) and the host was investigated after repeated intravesicular BCG-therapy for superficial bladder cancer. Studies were performed on (a) the local reaction in the bladder, (b) the systemic reaction, and (c) short and long term interactions in both the bladder and the serum/plasma.The analytes measured included anti-BCG IgA and IgG, fibronectin, lactoferrin, elastase-oci-proteinase inhibitor, myeloperoxidase and oc 2 -proteinase inhibitor. All analytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Our present data suggest that early IL-8 induction is important for subsequent development of an immune response and thus may be, indirectly, involved in the antitumor efficacy of BCG therapy. Possibly IL-8 acts by attracting neutrophils to the bladder, after which these activated cells facilitate BCG invasion and/or leukocyte infiltration by proteolytic enzyme production [14]. In addition, apart from the traditional involvement in inflammatory response, these neutropils could significantly influence the immune and antitumor response by the release of cytokines [4].…”
Section: Horizontal Bars Indicate Median Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present data suggest that early IL-8 induction is important for subsequent development of an immune response and thus may be, indirectly, involved in the antitumor efficacy of BCG therapy. Possibly IL-8 acts by attracting neutrophils to the bladder, after which these activated cells facilitate BCG invasion and/or leukocyte infiltration by proteolytic enzyme production [14]. In addition, apart from the traditional involvement in inflammatory response, these neutropils could significantly influence the immune and antitumor response by the release of cytokines [4].…”
Section: Horizontal Bars Indicate Median Valuesmentioning
confidence: 99%
“…Since a rapid influx of neutrophils after BCG instillation is observed in the urine of bladder cancer patients [5], we considered that IL-8, produced by urothelial cells in response to BCG exposure, could be responsible for the attraction of these neutrophils. Locally attracted and activated neutrophils can produce cytokines and proteolytic enzymes [4,14], which could possibly result in facilitated bladder wall infiltration by leukocytes and/or BCG and enhancement of the immune response. In this manner IL-8 production by urothelial cells might be important for the subsequent development of an immune response against BCG and associated clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, infiltration of T cells is not observed when heat-killed BCG is instilled into mouse bladders 7 , suggesting that heat-killed BCG cannot replace live BCG to treat BC patients. The systemic immune reaction after the intravesical instillation of BCG is less well understood, although previous studies have shown that cellular and humoral systemic responses could have a role in or be used as markers of the efficacy of BCG therapy 7 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…De Boer u. a. zeigten einen massiven Anstieg von neutrophilen Granulozyten im Urin von Patienten, mit einem Maximum am Tage der BCG-Instillation und an den folgenden zwei Tagen [9]. Die Freisetzung von Granulozyten assoziierten Enzymen, wie Myeloperoxidase, Collagenase, Elastase und Lactoferrin [10] konnte ebenfalls nachgewiesen werden und wurde als eine mögliche Ursache der BCG-induzierten Nebenwirkungen gesehen [11]. Aus diesem Grunde schlossen wir, dass die lokalen BCG-induzier-ten Nebenwirkungen überwiegend durch Granulozyten hervorgerufen werden.…”
unclassified